Analysis of Intrinsic Elements in The Film Ily From 38,000 Ft Director Asep Kusdinar - Ratna Puri Handayani; Nurhadi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research is a qualitative descriptive study using the subject of the film ILY From 38,000 Ft, directed by Asep Kusdinar and produced by Legaly Pictures, which aims to describe the intrinsic and extrinsic elements of the film. Data collection techniques use viewing techniques which are carried out by looking and listening carefully and repeatedly to the entire content of the film and documentation techniques are carried out by taking pictures (screenshots), cutting videos into the film. This research is motivated by the phenomenon of many films in Indonesia, 70% of which are based on or adapted from novels. The results of this research are the intrinsic and extrinsic elements contained in the film ILY From 38,000 Ft and the story depicted by the director ends with a happy ending.